The study of the Bible in the Middle Ages - Smalley, Beryl, 1905-1984 (University of Notre Dame Press, 1964)
Describes the changes in the organization, technique and purpose of Bible studies in northwestern Europe from the Carolingian Renaissance to about 1300. This was the period when the emergence of Aristotelian thought inspired medieval scholars to take a fresh look at the Scriptures.